Addressing Harm in Healthcare: A Responsive Perspective - Berber Laarman (Utrecht Law Review)
The Dutch legal framework that addresses the response to harm in healthcare falls short in meeting the needs of both patients and healthcare professionals. The adversarial nature of legal procedures often exercabates the initial harm of patient safety incidents for patients and healthcare professionals, who can be second victim of the incident. In this paper, a responsive perspective is used to explore how the response to patient safety incidents can be better aligned with the needs of patients and healthcare professionals. A responsive approach takes into account the specifics of each situation, the needs of the people involved, and the consequences of legal decisions for society. Analysis of complaint law and self regulation in healthcare demonstrates a shift in thinking from reactive to proactive claim management. Proactive claim management is further explored through the examples of Communicate and Resolution Programmes in the US and the principles of Restorative Justice.